Discovery of Natural Products as Novel and Potent FXR Antagonists by Virtual Screening - Diao, Yanyan; Jiang, Jing; Zhang, Shoude; Li, Shiliang; Shan, Lei; Huang, Jin; Zhang, Weidong; Li, Honglin (Frontiers in Chemistry, 2018)
Farnesoid X receptor (FXR) is a member of nuclear receptor family involved in multiple physiological processes through regulating specific target genes. The critical role of FXR as a transcriptional regulator makes it a promising target for diverse diseases, especially those related to metabolic disorders such as diabetes and cholestasis. However, the underlying activation mechanism of FXR is still a blur owing to the absence of proper FXR modulators. To identify potential FXR modulators, an in-house natural product database (NPD) containing over 4000 compounds was screened by structure-based virtual screening strategy and subsequent hit-based similarity searching method. After the yeast two-hybrid (Y2H) assay, six natural products were identified as FXR antagonists which blocked the CDCA-induced SRC-1 association. The IC50 values of compounds 2a, a diterpene bearing polycyclic skeleton, and 3a, named daphneone with chain scaffold, are as low as 1.29 μM and 1.79 μM, respectively. Compared to the control compound guggulsterone (IC50 = 6.47 μM), compounds 2a and 3a displayed 5-fold and 3-fold higher antagonistic activities against FXR, respectively. Remarkably, the two representative compounds shared low topological similarities with other reported FXR antagonists. According to the putative binding poses, the molecular basis of these antagonists against FXR was also elucidated in this report.